The management of pancreatic metastasis from synovial sarcoma of the soft tissue: A case report - Malek, Bouhani (Rare Tumors, 2020)
Pancreatic metastases are rare, accounting for 2%–3% of pancreatic tumors. The pancreas represents an unusual metastatic site of synovial sarcoma (SS) outside the usual localizations (regional nodes, lung, bone, and liver). The diagnosis is evoked by the personnel medical history of SS and imaging then confirmed by histological examination of the guided pancreatic biopsy. Its therapeutic management is mainly surgical with extensive removal of the lesion. So far only four cases have been reported in the English literature. We reported the case of a male aged 30-year-old who was admitted to our Institute for a local recurrence of SS of the left thigh which was initially treated by surgical excision. The patient underwent a wide surgical excision followed by chemotherapy and radiotherapy. About 15 months later, he experienced a pancreatic metastasis of his SS. He had a caudal splenopancreatectomy with partial resection of the transverse colon followed by chemotherapy. This report highlights the diagnostic difficulties of this rare localization and therapeutic challenge.